Structure and replication cycle of a virus infecting climate-modulating alga Emiliania huxleyi - Homola, Miroslav; Büttner, Carina R; Füzik, Tibor; Křepelka, Pavel; Holbová, Radka; Nováček, Jiří; Chaillet, Marten L; Žák, Jakub; Grybchuk, Danyil; Förster, Friedrich; Wilson, William H; Schroeder, Declan C; et al. (Science advances, 2024)
The globally distributed marine alga Emiliania huxleyi has cooling effect on the Earth's climate. The population density of E. huxleyi is restricted by Nucleocytoviricota viruses, including E. huxleyi virus 201 (EhV-201). Despite the impact of E. huxleyi viruses on the climate, there is limited information about their structure and replication. Here, we show that the dsDNA genome inside the EhV-201 virion is protected by an inner membrane, capsid, and outer membrane. EhV-201 virions infect E. huxleyi by using fivefold vertices to bind to and fuse the virus' inner membrane with the cell plasma membrane. Progeny virions assemble in the cytoplasm at the surface of endoplasmic reticulum-derived membrane segments. Genome packaging initiates synchronously with the capsid assembly and completes through an aperture in the forming capsid. The genome-filled capsids acquire an outer membrane by budding into intracellular vesicles. EhV-201 infection induces a loss of surface protective layers from E. huxleyi cells, which enables the continuous release of virions by exocytosis.
Keywords: Virion; Viruses; Phycodnaviridae; virion; viry; Climate; Haptophyta; podnebí